ANALISIS KRITIS TENTANG POLEMIK IMAM ALGHAZALI DAN IBNU RUSYD TENTANG KEBANGKITAN JASMANI (Jurnal Pelangi : Research of Education and Development, 2011)
Sritical analysis of the polemic of imam ghazali and Ibnu rusyd about the physical punishmenton the judgement day eventhough. Iman Al-ghazali and Ibnu rusyd have different ideals andarguments about the punishment all the judgement day, both of them have a great contribution tothe progress of Islamic thought. Rationally, it can be said that Ibnu rusdy has encounter Alghazalycriticsm, but from the affection of Islamic world, Al-ghazaly more powerful that Ibnurusdy. The latest philosopher is well know and he also called “hujjat al islam”.